Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1007/s10461-015-1188-6
|View full text |Cite
|
Sign up to set email alerts
|

Mobilization for HIV Voluntary Counseling and Testing Services in Vietnam: Clients’ Risk Behaviors, Attitudes and Willingness to Pay

Abstract: A multi-site survey was conducted on a sample of 365 clients to assess their willingness to pay for HIV voluntary counseling and testing (VCT) services in Ha Noi and Nam Dinh province, two epicenters of Vietnam. By using contingent valuation technique, the results showed that most of respondents (95.1 %) were willing to pay averagely 155 (95 % CI 132-177) thousands Vietnam Dong (~US $7.75, 2013) for a VCT service. Clients who were female, had middle income level, and current opioid users were willing to pay le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 24 publications
1
25
0
Order By: Relevance
“…For screening depressive symptoms, the Patient Health Questionnaire (PHQ-9) was used as a validated tool. Several previous studies were performed that used the Vietnamese version of this instrument to assess the depressive symptoms in different populations [20,26,27]. The PHQ-9 has 9 items about the frequency of depression-related symptoms that the respondents were bothered with in the last two weeks until the interview, which was consistent with the diagnostic standard of the Diagnostic and Statistical Manual of Mental Disorders, 5th Edition (DSM-V).…”
Section: Instrumentsmentioning
confidence: 99%
“…For screening depressive symptoms, the Patient Health Questionnaire (PHQ-9) was used as a validated tool. Several previous studies were performed that used the Vietnamese version of this instrument to assess the depressive symptoms in different populations [20,26,27]. The PHQ-9 has 9 items about the frequency of depression-related symptoms that the respondents were bothered with in the last two weeks until the interview, which was consistent with the diagnostic standard of the Diagnostic and Statistical Manual of Mental Disorders, 5th Edition (DSM-V).…”
Section: Instrumentsmentioning
confidence: 99%
“…In our study, based on the bidding method, the husbands were willing to pay US$14.5 and US$9.7 for HIV and syphilis screening tests, respectively while the payment scale method suggested lower WTP for both (US$10 and US$7.4). However, previous studies showed lower WTP prices among high-risk populations for an HIV test: US$5 in Peru [18], US$7.75 in Vietnam [15], US$2 in Kenya [16] and US$4.8-8.1 in China [13]. The general population in China was willing to pay US$8 [17] and students in Kenya US$3.2 [19].…”
Section: Discussionmentioning
confidence: 94%
“…The second section obtained the history of HIV and/or syphilis screening tests and knowledge of HIV prevention using the United Nations General Assembly Special Session on HIV/AIDS (UNGASS) score (0-3, low; 3-4, moderate; 5, high). Based on the evidence from literature, the age [16], income [13,16], educational level [16,[18][19][20], history of having a child [16], history of STI screen tests [16,18,21], and knowledge of HIV prevention [16] were considered potential factors affecting WTP and willingness to test for STIs. Other potential determinants such as the number of ANC visits [20] were excluded because they were beyond the scope of this survey.…”
Section: Questionnaire Developmentmentioning
confidence: 99%
“…To assess sexual activities, patients were asked about how often they had sexual intercourse, the number of sexual partners they had in the last 12 months, the types of sexual partner(s) they had (primary, casual, commercial) in the last 12 months, and condom use during the last sexual encounter with each type of partner. These measures have been successfully applied in the previous studies in different populations namely MMT patients and clients in HIV testing and counseling services (HTC) [ 16 , 19 , 20 ]. Patients had sexual risk behaviors when they had two or more sexual partners and did not use condom with their casual partners/ sex workers.…”
Section: Methodsmentioning
confidence: 99%